Healthcare strategic management and the resource based view. Issue 3 (12th August 2014) - Arbab Kash, Bita; Spaulding, Aaron; D. Gamm, Larry; E. Johnson, Christopher
Abstract : Purpose: – The purpose of this paper is to examine how two large health systems formulate and implement strategy with a specific focus on differences and similarities in the nature of strategic initiatives across systems. The aim is to gain a better understanding of the role of resource dependency theory (RDT) and resource based view (RBV) in healthcare strategic management. Design/methodology/approach: – A comparative case study design is used to describe, categorize and compare strategic change initiatives within a children's health and a multi-hospital system located in two competitive metropolitan markets. A total of 61 in-person semi-structured interviews with healthcare administrators were conducted during 2009. Summary statistics and qualitative content analysis were employed to examine strategic initiatives. Findings: – The two health systems have as their top initiatives very similar pursuits, thus indicating that both utilize an externally oriented RDT method of strategy formulation. The relevance of the RBV becomes apparent during resource deployment for strategy implementation. The process of healthcare strategic decision-making incorporates RDT and RBV as separate and compatible activities that are sequential. Research limitations/implications: – Results from this comparative case study are based on only two health systems. Further, the RBV perspective only takes managerial resources and time into consideration. Practical implications: – Given that external resources are likely to become more constrained, it is important that hospitals leverage relevant internal resources, in the identification of competitive advantages and effective execution of strategic initiatives. Originality/value: – The author propose a refined healthcare strategic management framework that takes both RDT and RBV into consideration by systematically linking strategy formulation with deployment of resources.